PERSEPSI SISWA MADRASAH ALIYAH AL-MUHLISIN TERHADAP PENERAPAN PEMBELAJARAN EKONOMI SYARIAH YANG BERKELANJUTAN - Toyib; Rahmat , Muhammad Imdadun; Casmita Pujiharto, Yaya Ruhenda (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2025)
This study aims to examine the perceptions of students of Madrasah Aliyah Al-Muhlisin regarding the implementation of sustainable sharia economic learning. The method applied in this study is quantitative descriptive, with data collection carried out through questionnaires and interviews. The sample analyzed consisted of 48 students, taken using purposive sampling techniques. The data obtained were analyzed using descriptive statistical techniques, assisted by SPSS software. The results of the study indicate that students' perceptions of sustainable sharia economic learning are relatively positive. The majority of students believe that the teaching methods used are quite effective in improving their understanding of sharia economic concepts. Many factors influence students' understanding, including the teaching approach applied by teachers, the availability of teaching materials, and the existence of direct practice in everyday life. The validity test shows that all items in the questionnaire are valid. Meanwhile, the reliability test of variable X (Student Perception) produces a Cronbach's Alpha value of 0.300 and variable Y (Sustainable Sharia Economic Learning) produces a Cronbach's Alpha value of 0.286, indicating that the research instrument has high reliability. In addition, the results of the simple linear regression analysis produced a constant value of 57.603 with a positive value, this can be interpreted that the variables Student Perception (X), and Sustainability of Islamic Economic Learning (Y) are constant and will experience an increase in sustainability of 57.603%. This study recommends that schools improve the quality of Islamic economics teaching by providing more comprehensive teaching materials and training for teachers so that teaching methods become more innovative. Students are also expected to be more active in seeking additional references and being involved in activities related to Islamic economics. Future research is expected to expand the scope of the study by using more in-depth methods.